(untitled) (Research, Society and Development, 2022)
The objectives were to estimate the prevalence of Alcohol Use and Alcohol-Related Problems and relate it to sociodemographic characteristics. A population-based cross-sectional study was carried out with 1,036 Maxakali aged nine years and older. A questionnaire was applied to 66 indigenous leaders about alcohol consumption in 2016 and its negative consequences. The association between the study objects was examined by applying the chi-square test, Fisher’s exact test, and cluster analysis. Kappa values ​​were calculated to assess questionnaire reproducibility. The 12-month prevalence was 39.1%. The use rate of women (17.3%) was 3.6 times lower than the rate of men. Male alcohol use rates increase from 8.1% to 64% in the 9-14 to 15-19 age group. The highest proportions of alcohol use between mothers and fathers were found in extended families and associated with the negative consequences of those who use cachaça. Female use begins between 20 and 24 years of age, and the rates of problems related to this use exceed those of men aged 25 to 45 years. It is expected that the ease of application and the predictive power of this tool will allow the detection and monitoring of alcohol use and its consequences in the Maxakali people.